Central bank liquidity provision, risk-taking and economic efficiency - Ulrich Bindseil; Juliusz Jabłecki (European Central Bank (ECB), 2013)
After the Lehman default, but also during the euro area sovereign debt crisis, central banks have tended to extend the ability of banks to take recourse to central bank credit operations through changes of the collateral framework (e.g. CGFS, 2008 - in consistence with previous narratives, such as Bagehot, 1873). We provide a simple four sector model of the economy in which we illustrate the relevant trade-offs, derive optimal central bank collateral policies, and show why in a financial crisis, in which liquidity shocks become more erratic and the total costs of defaults increase, central banks may want to allow for greater potential recourse of banks to central bank credit. The model also illustrates that the credit riskiness of counterparties and issuers is endogenous to the central bank's credit policies and related risk control framework. Finally, the model allows identifying the circumstances under which the counterintuitive case arises in which a relaxation of the central bank collateral policy may reduce its expected losses.
Keywords: E58; G32; 330; Central Bank; collateral policy; economic efficiency; Risk-taking